The effects of silkworm cocoon (Bombyx mori) wound dressing applications to the COX-2 expression and the number of neutrophils after skin excision wounds (in vivo research on Wistar rats) - Tarigan, Efron Andre (F1000 Research Ltd, 2022)
Background: Silkworm cocoons are materials that have fine regenerating abilities for the human body. Fibroin and sericin present in silkworm cocoons (Bombyx mori) are thought to have anti-inflammatory effects. This study aimed to know the effects of the use of wound dressing from silkworm cocoons toward COX-2 expression and neutrophils number in the inflammatory phase after skin excision. Methods: Twelve male Wistar rats according to inclusion criteria were randomly divided into 4 groups, each group of 6, based on the decapitation time (the 3rd day and the 6th day) and based on the dressing material (moist gauze dressing as the control group and silkworm cocoons as the treatment group). Each group was performed an excision on the dorsal skin with subcutaneous depth using a 4 mm-round punch biopsy. Neutrophil cell observations were performed by Hematoxylin eosin staining (HE). COX-2 expression was found in preparations for immunohistochemical staining using rabbit monoclonal COX-2 antibody at sacrificed period on the 3rd and the 6th day after wound dressing application. Results: The number of neutrophils and expression of COX-2 were analyzed using Two-way ANOVA and Independent t-test. The results showed a significant decrease in the number of COX-2 expression on inflammatory cells as well as the number of neutrophils (p<0.005) in the groups treated with wound dressing from silkworm cocoons on both the 3rd and 6th day. Conclusions: It was concluded that the use of wound dressing from silkworm cocoons can inhibit COX-2 expression (p=0,000) and decrease the number of neutrophils in the inflammatory phase after skin excision (p=0,001).